IAG Scientific Assembly 2025 - José Antonio, Tarrío Mosquera; Miguel, Marten Allendes; Catalina, Cáceres Venegas; Valeria, Vásquez Tejo; Juan, Giglio Gutiérrez; Marcelo, Caverlotti Silva; Alberto, da Silva; Laura, Sanchez; Sonia, Alves Costa; Nilton, Ribas Junior; María Virginia, Mackern; Micaela, Carbonetti; et al. (Usach, 2025)
Poster y presentacion en el congreso IAG Scientific Assembly 2025
Keywords: Otras Ingenierías y Tecnologías; Geodesia